HUBUNGAN ANTARA INGROUP FAVORITISM DAN PERILAKU PROSOSIAL - Alimin, Asep; Musthofa, Muhammad Ariez (Program Studi Psikologi Universitas Pendidikan Indonesia, 2019)
This research is aimed to correlate ingroup favoritism and prosocial behavior in religion intergroup relationship context. Pearson’s correlation was used to correlate them. The participants of this study were 103 muslims. Ingroup favoritism was measured by the Three Dimensions of Social Identification constructed by Cameroon (2004) and prosocialness behavior was measured by the adapted version of Prosocialness for Adults (PSA) by Caprara et. al. (2005). The study showed that there was a relationship between ingroup favoritism and prosocial behavior towards Muslims with a correlation coefficient of 0.23 and a p-value less than 0.005, and towards non-Muslims with a correlation coefficient of -0.416 and a p-value less than 0.005. Prosocial behavior was more frequently given by Muslims towards fellow Muslims compared to non-Muslims.